The Influence of Flash Sale Promos on Gen-Z Shopping Behavior on the TikTok Shop Marketplace Platform - Didik Himmawan; Ririn Ropiah (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study examines the role of marketplaces in online shopping among Gen-Z, particularly on the TikTok Shop platform. The goal of this study is to help Gen-Z use the platform wisely by understanding its advantages and disadvantages. Quantitative research was used, collecting data through interviews, observations, and a Google Form questionnaire with Islamic Education students at Wiralodra University. The results show that TikTok Shop has become a popular platform among Gen-Z due to its ease of access, significantly lower prices, and the strong influence of digital trends such as FOMO. However, there have been negative impacts on traditional markets, including a drastic decline in revenue. Furthermore, challenges with the delivery system and the risk of counterfeit goods fraud pose challenges for users. In conclusion, TikTok Shop plays a significant role in changing Gen-Z shopping behavior, but careful transaction processing is required to avoid losses.